Analisis Sistem Pengambilan Keputusan Terhadap Risiko Keselamatan Kerja Dan Lingkungan Kerja Dalam Bongkar Muat Kapal Pada PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur Dengan Menggunaka Metode Analytical Hierarchy Process (AHP) - Wahyudi, Indra; Muhammad, Abulwafa; Ariandi, Vicky (Riset Sinergi Indonesia (RISINDO), 2025)
This study aims to analyze the decision-making system related to occupational safety and environmental risks in the loading and unloading activities of ships at PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur. With the increasing complexity and risks faced in port operations, it is essential to apply a systematic method in decision-making. The Analytical Hierarchy Process (AHP) method was chosen as an analytical tool to evaluate various factors affecting safety and environmental work.Through this research, data were collected from loading and unloading activities over the past five years, which included an analysis of potential risks. The results of the study indicate that the application of AHP can assist in identifying and prioritizing risk factors, as well as providing recommendations for more effective hazard control. This research also found that with a good decision-making system, PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur can enhance occupational safety and minimize negative impacts on the environment. From the analysis results, it is hoped that this research can make a significant contribution to the development of risk management systems in the port sector and serve as a reference for other companies in managing occupational safety and the environment.